Synthesis and characterization of water-soluble polyaniline for hydrazine detection / Hazira Hussin - Hazira , Hussin (2020)
In this study, polyaniline (PAni) was synthesized through the chemical oxidation method using aniline (Ani) as a monomer, hydrochloric acid (HCl) as a dopant, and ammonium persulphate (APS) as an initiator. PAni was rendered water soluble through treating with cellulose derivatives. Cellulose derivatives such as methylcellulose (MC), hydroxypropyl cellulose (HPC), and hydroxypropyl methylcellulose (HPMC) were used as a stabilizer to improve the solubility of PAni in an aqueous medium. The water-soluble PAni-cellulose derivative was applied as a chemical sensor for hydrazine detection. The chemical structures and electrical conducting behaviours of PAni-cellulose derivatives were investigated using Fourier transform infrared (FTIR) and Ultraviolet- visible (UV-Vis) spectroscopic analyses. The conductivities of water-soluble PAni-cellulose derivatives were measured using conductivity meter. In calibrating the hydrazine detection, water-soluble PAni-cellulose derivatives were mixed with various concentrations of hydrazine and the sensor responses were measured using the conductivity meter. At the early stage of the application, the range from 10 ppm to 100 ppm of hydrazine concentration was used. There were several parameters that have been studied, these include: (i) different volume ratio of PAni to hydrazine, (ii) different types of cellulose derivatives, (iii) different mass ratio of Ani to MC, and (iv) the detection at different concentration of hydrazine (1 ppm to 10 ppm). From the results obtained, all water-soluble PAni-cellulose derivatives showed a decrease in the electrical conductivities with the increasing of hydrazine concentration. This happens due to the reduction of PAni from conducting emeraldine salt (ES) to non-conducting leucoemeraldine (LE) by hydrazine. The PAni-MC (ratio 2:5) showed the best result with a good linearity of 0.9832, hence was selected to study the sensor performance. The calibration plot was constructed from 0.05 ppm to 5.00 ppm of hydrazine. From the calibration curve, it showed a good linear correlation determination of 0.9953, a good sensitivity of 0.0132 ppm-1, the limit of detection (LOD) of 0.55 ppm, and the limit of quantitation (LOQ) of 1.82 ppm. This study showed that the LOD achieved was lower than the OSHA standard of 1 ppm. Besides, the sensor performance was supported by UV-Vis and FTIR analyses. UV-Vis spectra show a significant decrease in absorbance at the bipolaron band (~821 nm) from 3.27 to 0.63 and at polaron band (~450 nm) from 2.89 to 0.55. A notable change in the chemical structures analyzed by FTIR for the quinoid to benzenoid (IQ / IB) intensity ratio of 1.03 before the addition of hydrazine decreased to 0.97 after the addition of hydrazine. Both UV-Vis and FTIR analyses significantly proved that the ES of water-soluble PAni-MC has turned to LE because LE consists of the more benzenoid units compared to ES. The water-soluble PAni-MC eventually indicated a good recovery range of 96 - 136 % and a good relative standard deviation (RSD) of 2.69 - 5.84 % in the real sample analysis study. As a conclusion, the water-soluble PAni-MC showed good potential as a chemical sensor for hydrazine detection.